Aging alters the details recollected from emotional narratives. Issue 1 (2nd January 2023) - Agostino, Caterina; Sheldon, Signy
ABSTRACT: Although it is known that aging impairs episodic memory, the precise effect of aging on emotional memory is not fully understood. In this study, younger and older adults listened to narratives that contained general and emotional (positive, negative, or neutral) details as they viewed related images. When participants later recalled the narratives, both age groups remembered more emotional details from the negative than the positive or neutral narratives. Interestingly, the enhanced recall for the negative narratives came with a reduced ability to remember the associated images for both younger and older adults. For all narrative types, older adults recalled a similar number of general but fewer emotional details than younger adults. Although there were no age-specific emotional effects, memory functioning of the older adults related to better recall of the positive narratives and associated images. These results provide insight into the similarities and differences in how younger and older adults encode and retrieve complex emotional memories.